Alpha-glucans from bacterial necromass indicate an intra-population loop within the marine carbon cycle - Irena Beidler; Nicola Steinke; Tim Schulze; Chandni Sidhu; Daniel Bartosik; Marie-Katherin Zühlke; Laura Torres Martin; Joris Krull; Theresa Dutschei; Borja Ferrero-Bordera; Julia Rielicke; Vaikhari Kale; et al. (Nature Communications, 2024)
Abstract Phytoplankton blooms provoke bacterioplankton blooms, from which bacterial biomass (necromass) is released via increased zooplankton grazing and viral lysis. While bacterial consumption of algal biomass during blooms is well-studied, little is known about the concurrent recycling of these substantial amounts of bacterial necromass. We demonstrate that bacterial biomass, such as bacterial alpha-glucan storage polysaccharides, generated from the consumption of algal organic matter, is reused and thus itself a major bacterial carbon source in vitro and during a diatom-dominated bloom. We highlight conserved enzymes and binding proteins of dominant bloom-responder clades that are presumably involved in the recycling of bacterial alpha-glucan by members of the bacterial community. We furthermore demonstrate that the corresponding protein machineries can be specifically induced by extracted alpha-glucan-rich bacterial polysaccharide extracts. This recycling of bacterial necromass likely constitutes a large-scale intra-population energy conservation mechanism that keeps substantial amounts of carbon in a dedicated part of the microbial loop.